Correlates and Predictors of Employee Turnover Intentions in the Postal Industry! A Case Study of the Omaha Hub of United Parcel Service - Garay, Carla Y (2002)
The purpose of this study was to identify the correlates and predictors of turnover intentions among manual laborers. The study was exploratory and used a modification of the Rusbult and Farrell (1983) investment model as its theoretical framework. Simple correlation analysis uncovered no significant relationships between the fifteen independent variables and turnover intention, with one exception; there was a significant correlation between intent to retire and turnover intention. Therefore, further analysis was conducted by testing each independent variable against each item of turnover intentions. The independent variables that were found to be significantly correlated with the items of turnover intentions were then entered into a regression analysis to test for predictive potential. Of the independent variables that were included in the regression analysis, three emerged as predictors of various items of turnover intentions at the .05 level of significance: Alternatives, distributive justice, and active pursuit o f degree. Of those, alternatives is the only one that showed a pattern of predictability. The Rusbult and Farrell model posits that job costs and job rewards lead to satisfaction which, along with alternatives and investments, predict commitment, of which turnover is a function. However, the present study found, to the contrary, that among manual laborers, job costs, job rewards, job satisfaction, and investment had no effect on turnover intent. Instead, the variable perception of alternatives was the only one that predicted turnover intentions. One reason these findings differ from those of previous research may be the fact that turnover literature has largely overlooked the category of manual laborers, which is structurally dissimilar from the traditionally studied categories of workers